Sikap Keuangan Dan Pengetahuan Keuangan Terhadap Kemampuan Keuangan: Peran Perilaku Keuangan Pada Sektor Usaha Produk Halal - Kusuma, Desta Rizky; Fikri, Muhammad Ali; Putra, Ulinnuha Yudiansa (ITB AAS INDONESIA Surakarta, 2023)
Financial literacy is one of the important aspects for organizations to be able to manage their financial resources optimally. This study aims to determine the effect of financial attitude, financial knowledge, and financial inclusion on financial ability with financial behavior as a mediating variable. This study used a sample of 180 from Micro, Small and Medium Enterprises (MSMEs) in the halal product business sector. The data processing technique used in this study is the structural model equation technique using the Smart PLS 3.0 software. The results showed that financial attitude has a positive effect on financial behavior, financial knowledge has a positive effect on financial behavior, financial behavior does not have a positive effect on financial capability, financial attitude does not have a positive effect on financial capability, financial knowledge does not have a positive effect on financial capability, financial behavior does not mediate the positive effect of financial attitude on financial capability, financial behavior does not mediate on the positive effect of financial knowledge on financial capability.